2008
DOI: 10.1016/j.nurt.2007.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Current Status of Symptomatic Medical Therapy in Parkinson’s Disease

Abstract: Summary: Symptomatic medical therapies for Parkinson's disease (PD) have been disease modifying and have led to improvement in daily function, quality of life, and survival. For 40 years, these therapies have been primarily dopaminergic, and currently include the dopamine (DA) precursor levodopa (LD), DA agonists, catechol-O-methyltransferase (COMT) inhibitors, and monoamine oxidase (MAO) inhibitors. The roles of all these classes of agents have evolved, with significant changes occurring since the early 2000s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 147 publications
0
30
0
Order By: Relevance
“…Recent work has also revealed deficits in other brain regions necessary for locomotor control (Mena-Segovia et al, 2004) (Bloem et al, 2001; Bohnen and Albin, 2011; Factor, 2008; Grabli et al, 2012; Melton et al, 2006). In particular, recent attention has focused on the neuroanatomy of brainstem areas including the pedunculopontine nucleus (PPN), which degenerates in PD as well as in related disorders such as progressive supranuclear palsy (Lee et al, 2000).…”
Section: Neuromechanics Of Motor Impairment and Rehabilitationmentioning
confidence: 99%
“…Recent work has also revealed deficits in other brain regions necessary for locomotor control (Mena-Segovia et al, 2004) (Bloem et al, 2001; Bohnen and Albin, 2011; Factor, 2008; Grabli et al, 2012; Melton et al, 2006). In particular, recent attention has focused on the neuroanatomy of brainstem areas including the pedunculopontine nucleus (PPN), which degenerates in PD as well as in related disorders such as progressive supranuclear palsy (Lee et al, 2000).…”
Section: Neuromechanics Of Motor Impairment and Rehabilitationmentioning
confidence: 99%
“…Currently, LD, oral dopamine receptor agonists, and MAO B inhibitors are approved by the Federal Drug Administration (FDA) for use in early and advanced PD, while COMT inhibitors and the broad-spectrum injectable dopamine agonist, apomorphine, are approved only for fluctuating PD symptoms. Clinical trials have demonstrated the usefulness of these drugs under their approved conditions (Factor, 2008).…”
Section: Dopamine Replacement Therapymentioning
confidence: 99%
“…This dosage form is designed to disintegrate or dissolve rapidly on contact with saliva, thus eliminating the need for chewing the tablet, swallowing an intact tablet, or taking the tablet with water. This mode of administration would be beneficial to solve the problem of swallowing difficulty encountered by pediatric and geriatric patients, nauseated, psychiatric, bedridden patients, and those with parkinsonism (8)(9)(10). The main obstacles, however, encountered during ODT manufacturing include the high fragility of tablets necessitating the use of special packages and the employment of expensive equipment in the manufacturing process (10).…”
Section: Introductionmentioning
confidence: 99%